Application of PCR-SSP method for HLA-B*27 identification as an auxiliary tool for diagnosis of ankylosing spondylitis - Oliveira,Gisele Cristina A. (2016)
ABSTRACT INTRODUCTION: Human leukocyte antigens (HLA) are molecules that present antigen to the immune system; their presence or absence have been described as an influential factor in some diseases. HLA-B*27 is an HLA polymorphism that has been associated with increased susceptibility to ankylosing spondylitis (AS) and other spondyloarthropaty. The detection of HLA-B*27 has been used as diagnostic and prognostic tool in these cases, as well as in the differential diagnosis of other diseases. OBJECTIVE: Standardize the single specific primer-polymerase chain reaction (PCR-SSP) methodology for use in the Immunogenetics Laboratory of the Universidade Estadual de Maringá (UEM), considering its specificity and cost-effectiveness. MATERIAL AND METHODS: A total of 30 individuals without AS positive for HLA-B*27 allele and 10 AS negative individuals, were previously tested by PCR-sequence specific oligonucleotide (PCR-SSO) and, in this study, by PCR-SSP. RESULTS: One hundred percent of the patients tested confirmed their results, even with different subtypes. CONCLUSION: Considering the high reproducibility and the broad spectrum of subtypes covering, it was concluded that the PCR-SSP identifying method for HLA-B*27 can be used as a routine diagnostic tool for spondyloarthropathies.